Participatory Motivations in Advisory Councils: Exploring Different Reasons to Participate. - Costa-Font, Joan; Pasadas, Sara; Fernández-Martínez, José Luis (Taylor & Francis, 2021)
The most common participatory institution has been insufficiently analysed: associationally based institutions often exist at any government level (from the neighbourhood to the state), but have received only scant academic attention. This paper analyses these advisory councils (ACs) in Spain, in order to understand why their participants continue to attend the meetings, given the apparently limited attractiveness these institutions have. The analysis, based on results from a survey of participants (n = 569) in a sample of ACs (n = 70), shows that a diverse set of motivations exist (knowledge, influence, recognition and civic duty) and that the relevance of each of them varies within different types of councils and for different groups of participants. The results are relevant to the general discussion as to why people participate in different types of participatory institutions and in discussing how participatory inequalities appear in them.
https://openpolicyfinder.jisc.ac.uk/id/publication/6007
Keywords: Administración local - Opinión pública; Democracia directa; Advisory councils; Participatory democracy; Associative democracy